The moderating effect of firm size on corporate governance practices with firm’s capital structure - A. Abdlazez, Fahed (2016)
Risk of corporate failure exists in every industry in Malaysia and it is worsening in tandem with economic crisis in 1997. A total number of companies that are delisted from the last 25 years suggest that the delisting of companies is very high. The main reason for delisting of such companies was poor credit performance and lack of control. Clearly, firms are unable to face the unexpected changes in economic and fail to generate profit for the companies. In public-listed companies, shareholders are considered as the owner of the firm and it is important for the managers to work in the benefit of shareholders. In order to monitor managers to work ethically in protecting investors and becoming more transparent to outsiders, there is a need of corporate governance as a monitoring Practice for reducing agency conflict issues especially in making capital structure decisions. Thus, this study aimed to investigate the influence of corporate governance on capital structure among public-listed companies in Malaysia. Using the annual reports of 273 Malaysian public listed firms on the main board of Bursa Malaysia from the year 2008 to 2012, Hierarchical multiple regression analysis were conducted. Corporate governance practices were found to have positive influence on debt equity ratio, long term debt, short term debt and debt ratio of capital structure. However, corporate governance practices influence on debt ratio is not statistically significant. Firm size moderating the relationship between corporate governance variables and capital structure. These findings imply the importance of corporate governance practices to infuse better management practices, effective control and regulatory Practices for efficient utilization of firm’s resources.